Salinity, pH, and Temperature Effects on the Corrosion Rate of KI-A Steel Plates - Rifnia A. Utami; Agustinus Tupamahu; Debby R. Lekatompessy; Richard B. Luhulima (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Steel structures at tropical ferry ports deteriorate rapidly, yet field evidence on how salinity, pH, and temperature jointly govern the corrosion rate of shipbuilding-grade steel plates remains limited in eastern Indonesia. Objective: This study quantifies the corrosion rate of 8-mm KI-A steel plates immersed for two to eight weeks at Hunimua and Galala Ferry Ports, Ambon, and partitions the effects of immersion duration, location, salinity, pH, and temperature. Methods: Twenty-four coupons were exposed for weight-loss testing in accordance with ASTM G1. Data were analyzed using factorial ANOVA, two-sample t tests, and regression analysis at a significance level of 0.05. Results: Immersion duration had no significant effect (F = 0.49; p = 0.492), whereas location was highly significant (F = 33.93; p = 0.000) and explained 62.3% of the total variation. The mean corrosion rate reached 13.15 MPY at Hunimua compared with 7.42 MPY at Galala. Salinity (p = 0.000; R² = 60.0%) and pH (p = 0.000; R² = 46.65%) were significant in simple regression analyses but not in the multiple regression model (p > 0.05), indicating shared variance. Conclusion: Salinity and pH, rather than exposure duration, govern the corrosion of KI-A steel in tropical port waters. Cathodic protection and corrosion-resistant materials should be prioritized at high-salinity berths such as Hunimua, and further studies should measure dissolved oxygen, current velocity, and biofouling.